ANALYSIS OF IMPLEMENTATION DISCIPLINE IN IMPROVING EMPLOYEE PERFORMANCE IN CIAKAR VILLAGE OFFICE KABUPATEN TANGERANG - Laila Irawati; Ading Sunarto (Yayasan Education and Social Center, 2023)
This study aims to find out about the Analysis of the Application of Discipline in Improving Performance at the Ciakar Village Office, Tangerang Regency. The research method used is a type of qualitative research using a sampling technique, namely purposive sampling. Data collection techniques in this study used structured and unstructured interviews, observation, and documentation. Data analysis techniques in this study used SWOT analysis, observation and direct interviews with key informants and informants. The results of this study indicate that the implementation of work systematics at the Ciakar Village Office is quite good, but in terms of work discipline there are still some employees who take it lightly, starting from those who do not arrive on time, abuse of rest hours and many explanations for work responsibilities according to the job duties of each employee. The performance at the Ciakar Village Office is quite good, with team work or collaboration between employees but this very family-friendly organizational culture has resulted in employees not being professional in carrying out their duties and responsibilities